INTEGRASI FMEA DALAM PENERAPAN QUALITY CONTROL CIRCLE (QCC) UNTUK PERBAIKAN KUALITAS PROSES PRODUKSI PADA MESIN TENUN RAPIER - Yudi Syahrullah; Milenia Rahma Izza (Universitas Putera Batam, 2021)
PT. Pajitex is one of the textile industries that produce sarongs and continues to strive to fulfill customer desires through quality sarong products. During the sarong production process, there are still various product defects that can reduce consumer confidence in the resulting sarong products. Therefore, PT. Pajitex strives to reduce the number of defects that occur in the sarong manufacturing process by exploring various causes of defects. The purpose of this study was to analyze the defective edge on the CR3082 plate using the Quality Control Circle (QCC) method. The QCC method is a quality control system through the 8-step method with a continuous improvement system. At the defect search stage, use quality control tools such as Pareto diagrams and fishbone diagrams, and use the Failure Mode Effect Analysis (FMEA) method to obtain the highest RPN value which is a priority in the improvement proposal, and in determining the improvement proposal using the PDCA Methods. Based on the results of the analysis obtained, the cutter cutting and the needling process are not perfect and the tuck-in setting is not precise has the highest RPN value, which is equal to 120, so this activity needs to be monitored and followed up